Neuroscience and Fitrah Integration: Brain Mechanisms Shaping Contemporary Islamic Education and Holistic Learning - Metriadi Metriadi; Erizal Erizal; Zidni Ilman Nafian; Ahmad Lahmi; Julhadi Julhadi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study aims to analyze the mechanisms of the brain and nervous system in the learning process and to examine their relevance to the concept of fitrah in contemporary Islamic education. This study is motivated by emerging findings in neuroscience that explain the biological processes of learning, while Islamic education relies on the concept of fitrah as the foundation for the holistic development of human potential. However, studies that integrate these two perspectives remain relatively limited. The study employed a Systematic Literature Review (SLR) method in accordance with the PRISMA 2020 guidelines. Data were obtained by searching for scientific articles in the Google Scholar, Scopus, Dimensions, DOAJ, and Crossref databases published between 2020 and 2026. Literature meeting the inclusion criteria was analyzed using thematic synthesis techniques to identify patterns, concepts, and relationships among variables. The results indicate that attention, emotion, memory, executive function, and neuroplasticity are the primary brain mechanisms influencing learning success. This study found a conceptual common ground between neuroscience and Islamic education that paves the way for a more holistic learning paradigm. This model is expected to serve as a conceptual foundation for the development of evidence-based Islamic education including curriculum, learning strategies, and character education in the contemporary educational landscape.